Comparative study of brain activity and functional connectivity in blepharospasm and blepharospasm-oromandibular dystonia - Wang, Yanying; Luo, Min; Hou, Bo; Li, Yang; Yang, Yingmai; Feng, Feng; Wang, Lin; Wan, Xinhua (Frontiers in Neurology, 2025)
BackgroundThe most common spread of blepharospasm (BSP) is to the oromandibular region, labeled as blepharospasm-oromandibular dystonia (BOM). We aimed to identify shared and different functional changes in BSP and BOM, trying to unveil the pathogenesis of these disorders and the mechanism of dystonic spread.Materials and methodsThis single center study recruited 16 BSP patients, 16 BOM patients and 20 healthy controls (HC). Clinical information and resting-state fMRI images were collected. Dynamic amplitude of low-frequency fluctuations (dALFF) was calculated using the sliding window method. Intergroup differences in static ALFF (sALFF) and dALFF were examined. Using dALFF results, seed-based static and dynamic functional connectivity (FC) were constructed to compare connectivity changes in BSP and BOM networks. Correlations between dynamic parameters and disease severity scores were analyzed using Spearman partial correlation.ResultsCompared with HC, BSP and BOM presented increased dALFF in the bilateral basal ganglia, bilateral supplementary motor area, right precentral gyrus, and bilateral cingulate gyrus. BOM further demonstrated decreased sALFF in the left cerebellum. Compared with HC, BOM patients had decreased sFC in the network involving the sensorimotor cortex, supplementary motor area, basal ganglia, cerebellum, and brainstem. In addition, decreased dFC strength was found between the right pallidum and cerebellum. Comparing with BSP patients, BOM patients showed decreased sFC and dFC strength in a similar but limited pattern. Clinical scores of BSP severity were significantly correlated with dALFF in some of these important regions.ConclusionsOur results demonstrated common brain regions with impaired functional activity in BSP and BOM patients. Further, BOM is featured with widespread connectivity reduction in the sensorimotor cortico-basal ganglia-brainstem-cerebellar network deriving from these key regions. These findings could help investigate mechanisms of dystonia spread and potentially facilitate disease-modifying therapies.